Instructional Design in Open Distance Learning: Present Scenario in Pakistan: Muhammad Ajmal * Mahek Arshad ** Javaria Hussain*** (PJDOL, 2023)
Higher Education Commission, Pakistan established fourteen Distance Learning Directorates in formal universities to cater the need of education for external students through open distance learning. Open Distance Learning needs a compact instructional design mechanism which deals with Analysis, Design, Delivery, Improvement and Evaluation being practiced in these Open Distance Learning Directorates. The study aimed to determine the present scenario in Pakistan regarding instructional design practiced in open distance learning. Objectives of the study were to investigate the instructional design mechanism being practiced by open distance learning directorates established in formal institutes in Pakistan, to identify the problems faced by directorates of open distance learning and to propose indigenous students’ supportive instructional design mechanism for open distance learning in Pakistan.